Al-Mubâdalah fî Mafhûmi Fiqhi al-Mar‛ah al-Mu’âshirah bî Indûnîsiyâ - Siti Nurjanah; Agus Hermanto; Lutfiana Dwi Mayasari; Nety Hermawati (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
Man is a leader of the household, while the wife serves as the household manager. Generally, this paradigm is embedded in our society because men are always put as the main guard at the front while wives are always set in the limited area. Contextually, the problem is in the role of women which is no longer solely in the domestic sphere. Most of them also have a role outside the home to help husbands earn a living. The purpose of this study is to obtain a reconstruction of reciprocal fiqh (mubâdalah fiqh) principle in terms of rights and obligations of both husband and wife. This research is a literature review with a qualitative type using the reciprocal (mubâdalah) approach. The results of this study show that partners in realizing justice in the household, according to the mubadalah approach, are required to make mutual help through working together, such as mutual consultation, mutual democracy and mutual taking and giving in building harmonious relationship. الرجل هو رب الأسرة والزوجة ربة المنزل. هذا النموذج جزء لا يتجزأ من مجتمعنا بشكل عام، لأن الرجل هو الحارس الرئيسي وكان دائمًا في المقدمة بينما تكون الزوجات دائمًا في المنطقة المحدودة. وتكون المشكلة في أن دور المرأة لم يعد في المجال المنزلي فقط، بل معظمهن أيضًا لهن دور خارجَ المنزل لمساعدة الأزواج في كسب لقمة العيش. والسؤال كيف تتم حقوق وواجبات الزوج والزوجة في هذا السياق؟ الغرض من هذه الدراسة هو إعادة بناء الحقوق والالتزامات الجديدة التي تعكس مبادئ فقه المبادلة من حيث حقوق والتزامات الزوج والزوجة. هذا البحث عبارة عن مراجعة أدبية، ونوعي بمنهج التبادل (المبادلة). نتائج هذه الدراسة أن الشركة بين الرجل والمرأة في تحقيق العدالة في الأسرة يجب أن تكون مساعدة متبادلة في العمل معا مثل التشاور، والديمقراطية، والإحسان لبعضهم البعض في المعاملة